Bilinguismo e interpretação simultânea: uma análise cognitiva do processamento da memória de trabalho e da fluência verbal - Merode, Paola Davi Nolasco Rodrigues (2012)
The purpose of this investigation, which appears in the form of a comparative study, was to evaluate verbal fluency (VF) and to compare the differences in the processing capacity of the working memory (WM) of a bilingual individual, a simultaneous interpreter and a monolingual individual. Literature about bilingualism suggests a bilingual disadvantage in VF tests (BIALYSTOK, 2001, 2005, 2009) and similarities, in general, between bilingual and monolingual speakers in the performance of tests that measure WM processing (NAMAZI; THORDARDOTTIR, 2010), although there is no consensus on this (WODNIECKA et al., 2010). However, few studies have analyzed WM processing by simultaneous interpreters as a specific group of bilingual individuals. In this study, they are classified as a separate group because the nature of their activity requires not only the proficient knowledge of two languages, but also a complex and imbricate association of both that arises from an "interpretative competence". Simultaneous interpreters are believed to deal with many pieces of information during conference interpretation and, because of that, have a greater WM processing capacity than bilingual and monolingual individuals. It is also believed that lexical access by simultaneous interpreters may not be negatively affected by bilingualism, and that, rather, their VF test scores are similar to those of monolingual speakers, as this is an indispensable condition for their work. These assumptions were evaluated using verbal WM (Auditory Word Span and Auditory N-back tasks) and VF tests (Lexical Evocation) in Brazilian Portuguese, the mother language of all participants. The criteria for participant selection were age, sex, years of schooling, fluency and frequency of L1 (Portuguese) and L2 (English) use. The results indicate a similar performance between the interpreter and monolingual participants in the tests of VF, with a lower z score for bilingual. This similarity, however, was not observed in WM tests.